Kompetisi beberapa jenis gulma terhadap pertumbuhan awal beberapa varietas tanaman tebu (Saccharum officinarum L.) - Moelyaandani, Dentin Queentiara; Setiyono, S (Jurnal Proteksi Tanaman Tropis, 2020)
Sugarcane (Sacharum officinarum L.) is a sugar-producing plant and is a food commodity that is needed by the people of Indonesia. National sugar demands are increasing every year. The low productivity of sugarcane is due to the competition of weeds which can reduce sugarcane production. To achieve high productivity, it is necessary to pay attention to the varieties used because they require certain conditions in their management. The purpose of this study was to determine the effect of varieties and types of weeds on the initial growth of sugarcane. The study was conducted from September 2018 to December 2018. The study used factorial Randomized Block Design (RBD) with two factors and four replications. The first factor consists of 4 sugarcane varieties, namely: Bululawang (V1), Red HW (V2), VMC (V3) and PS 862 (V4). The second factor type of weed consists of 2 types, namely Cyperus rotundus (N1) and Amaranthus spinosus L. (N2). The results showed that (1) There was interaction between the varieties (V) and the weed types (N) in stem diameter parameters and number of tillers, the treatment V4N1 gives the best response to stem diameter 1,31 cm and 4,25 number of tillers; (2) The treatment of varieties (V) gives affects to stem diameter and number of leaves, the treatment V4 gives the best response 5,38 to number of leaves; (3) Types of thorn spinach weeds can reduce the initial growth of sugarcane. Keywords: Varieties; weed; sugarcane